Discerning Barth's Legacy: Sorting the Good Conflicts From the Bad. Issue 4 (November 2022) - Holmes, Christopher R.J.
In dialogue with Christiane Tietz's engrossing biography, this review essay addresses the different conflicts that characterize Barth's life. I discuss what conflicts we should be grateful for and what conflicts we should regret. My main interest is in how the story of Barth's personal and private life intersects with the story of his extraordinary theological career. My working assumption in this review is that there is an indirect line between his theology and his adultery.